2018
DOI: 10.1002/jcb.26423
|View full text |Cite
|
Sign up to set email alerts
|

Identification of over expressed proteins in oral submucous fibrosis by proteomic analysis

Abstract: Early detection and identification of oral pre‐malignancy or malignancy help in management of the disease and improve survival rates. Oral submucous fibrosis (OSMF) is a major threat to public health worldwide and especially in Southeast Asian countries. Identification of biomarkers is a necessary step toward early diagnosis and treatment. In this study, differentially expressed proteins between oral submucous fibrotic tissue and normal control tissues were recorded by proteomic analysis using two dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The proteins were categorized based on cellular localization, molecular function and biological process [32]. To the best of our knowledge, there was only one previously published Indian study on the proteomic analysis of OSMF and normal tissue that identified 15 upregulated genes, of which HSP-70, enolase and Lumican were also recognized in the current study [9]. However, our study, apart from samples from OSMF patients, additionally included patient samples with histologically proven OSCC along with OSMF and which were compared to normal patients, which helped in evaluating the target proteins involved in the malignant transformation of OSMF.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The proteins were categorized based on cellular localization, molecular function and biological process [32]. To the best of our knowledge, there was only one previously published Indian study on the proteomic analysis of OSMF and normal tissue that identified 15 upregulated genes, of which HSP-70, enolase and Lumican were also recognized in the current study [9]. However, our study, apart from samples from OSMF patients, additionally included patient samples with histologically proven OSCC along with OSMF and which were compared to normal patients, which helped in evaluating the target proteins involved in the malignant transformation of OSMF.…”
Section: Discussionmentioning
confidence: 83%
“…A total of 88 proteins with altered expression levels were identified, and cyclophilin A was proposed as a potential biomarker and therapeutic target for OSMF [8]. In addition, a study conducted in India showed differentially expressed proteins between OSMF and normal tissue by a proteome analysis with twodimensional electrophoresis and Matrix-Assisted Laser Desorption Ionization Imaging Time of Flight (MALDI TOF) mass spectrometry, which showed that 15 proteins were upregulated and that 10 proteins were downregulated in the OSMF tissues compared to normal tissue [9]. MALDI-IMS-based proteome analysis, used to analyse the differences in protein expression between OSCC tissues and adjacent non-cancerous OSMF tissues, showed nine differently expressed proteins, of which the expression of NCOA7 in OSCC tissues was upregulated by immunohistochemical staining and Western blotting and correlated with the clinicopathological parameters [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that macrophages are important regulators of tissue repair or fibrosis. 32 Macrophages produce different polarization directions after tissue damage activates the inflammatory response, resulting in changes in the substantive function of the surrounding cells and extracellular matrix (ECM), and the polarization direction of macrophages can determine whether the microenvironment is persistent inflammation (M1) or post-injury fibrosis (M2). 33 Studies have confirmed that M2 macrophages can directly affect the production of fibrosis by producing a large number of pro-fibrotic factors (TGF-β1), promoting the proliferation, survival, and activation of myofibroblasts; inflammatory cell migration; and excessive production of ECM.…”
Section: Relationship Of Osf With Macrophagementioning
confidence: 99%
“…found that OSF patients have significant immune cell infiltration in their tissue samples, among which macrophages were one of the main active cells. Studies have shown that macrophages are important regulators of tissue repair or fibrosis 32 . Macrophages produce different polarization directions after tissue damage activates the inflammatory response, resulting in changes in the substantive function of the surrounding cells and extracellular matrix (ECM), and the polarization direction of macrophages can determine whether the microenvironment is persistent inflammation (M1) or post‐injury fibrosis (M2) 33 .…”
Section: Relationship Of Osf With Immune Cellsmentioning
confidence: 99%
“…Studies have shown that the immune microenvironment of OSF significantly changes during OSF occurrence, including infiltration of immune cells of different subtypes and functions in the diseased tissue, as well as expression of immune‐related cytokines 5 . For example, Chiang et al found significant immune cell infiltration in tissues obtained from OSF patients, and macrophages were the main active cells.…”
Section: Introductionmentioning
confidence: 99%